Observation of the decay [Xi]−b→pK− K− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physical review letters, 2017)
Decays of the Ξ−b and Ω−b baryons to the charmless final states ph−h'−, where h(') denotes a kaon or pion, are searched for with the LHCb detector. The analysis is based on a sample of proton-proton collision data collected at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. The decay Ξ−b→pK−K− is observed with a significance of 8.7 standard deviations, and evidence at the level of 3.4 standard deviations is found for the Ξ−b→pK−π− decay. Results are reported, relative to the B−→K+K−K− normalization channel, for the products of branching fractions and b-hadron production fractions. The branching fractions of Ξ−b→pK−π− and Ξ−b→pπ−π− relative to Ξ−b→pK−K− decays are also measured.